Back to the wild: does feralization affect the mandible of non-commensal house mice (Mus musculus domesticus)?. (2nd February 2019) - Souquet, Louise; Chevret, Pascale; Ganem, Guila; Auffray, Jean-Christophe; Ledevin, Ronan; Agret, Sylvie; Hautier, Lionel; Renaud, Sabrina
Abstract: While domestication has been well studied, with the recent recognition of the so-called 'domestication syndrome', the opposite process, feralization, has received far less attention. The commensal Western European house mouse ( Mus musculus domesticus ) lives in close contact with humans, and as such it lies between wild and domesticated animals. However, it also occurs in non-anthropogenic environments, forming feral populations, and hence provides the opportunity to document how feralization may impact morphology. In this study, three 'feral' populations from Orkney, the Kerguelen Archipelago and southern France were compared to Western European commensal populations. The shape and biomechanical properties of the jaw were analysed to assess the impacts of 'feralization' on an organ that is under major environmental pressures through its feeding function. Mandible shape varied mostly with climate and phylogeny, and feral populations differed only slightly from their geographically close relatives. In contrast, feral mice shared a biomechanical signature corresponding to a decrease in the superficial masseter/molar mechanical advantage, suggesting poorer molar biting performance. This is interpreted as a parallel response to a relaxation of environmental pressure, possibly due to a diet shift in feral habitats.